Pengaruh Riwayat Keluarga, Obesitas Dan Stress Psikosial Terhadap Kejadian Hipertensi Pada Ibu Pasangan Usia Subur Di Wilayah Kerja Puskesmas Simalingkar - Lasria Simamora; Ninsah Putri Sembiring; Marlina Simbolon (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2019)
Hypertension a serious pubic health problem since it is directly related to morbidity and mortality rate. It is also a chronic disease which can cause complication which will eventually influence the process of womenâ€™s reproduction, especially of mother of eligible couples. It ranked the third of the top ten diseases in the working area of Simalingkar Community Health Center (â€œPuskesmasâ€), in 2016. The objective of the research was to find out which influenced of family history, obesity and psychosocial stress the incidence of hypertension of mother of eligible couples in the working area of Simalingkar Community Health Center. The research used observational analytic method with case-control study and retrospective design. The population was all productive-aged women in the working area of Simalingkar Community Health Center. The samples consisted of 68 respondents who were in the case group and the other 68 respondents in the control group, taken by using consecutive sampling technique. The data were analyzed by using univariate analysis, bivariate analysis with chi square test, and multivariate analysis with multiple logistic regression analysis. The result of the research showed that there was the influence of obesity p=0.003 (OR=2.95 CI 95% 1.438 â€“ 6.058 and psychosocial stress p=0,008 (OR=2,63 CI 95% 1,282 - 5,426) on the incidence of hypertension, while history of family did not have any influence on the incidence of hypertension in the working area of Simalingkar Community Health Center. Obesity was the most dominant factor which influenced the incidence of hypertension of mother of eligible couples at OR= OR=2.95 (p<0.05). It is recommended that the health care providers at Simalingkar Community Health Center provide adequate information about hypertension for the people who should routinely control their blood pressure, have healthy eating pattern and lifestyle and do exercises regularly in order to avoid hypertension.